PEMBUATAN ALAT PENJERNIHAN MINYAK JELANTAH DENGAN OTOMASI LAJU ALIR - Melysa Putri; Roswita; Faldi Lulrahman; Fardian (Prodi Teknologi Pangan Fakultas Pertanian Universitas Islam Indragiri, 2022)
Used cooking oil is oil obtained from repeated frying, so it is not healthy for consumption. In addition, used cooking oil can also cause environmental pollution if discharged directly into the environment. To overcome this problem, a used cooking oil purification device with flow rate automation was made. This study aims to make the used cooking oil purification process more effective. This used cooking oil processing equipment consists of a holding tank, a flow rate control device, a flow rate reader, an adsorption column containing cotton, activated charcoal, and zeolite. Then, the performance of the tool was tested. Based on the research that has been done, used cooking oil which was initially reddish brown and smelled rancid after being processed, the color changed to brownish yellow and the smell was slightly rancid. Therefore, it can be concluded that the used cooking oil purification equipment with flow rate automation is effective for purifying used cooking oil.